Teaching Geography in the Context of Combined Courses Across the Social Sciences: An Analysis of 50 years of Coexistence - Johann, Florian; Brühne, Thomas (Journal of Geography Education, 2021)
Since 1972, combined courses including different science subjects (e.g., social studies) have coexisted alongside the teaching of traditional singular social science subjects. Combined courses are currently being taught in thirteen federal states, and, in recent years, a public discussion has commenced about a more integrated approach of subjects and teaching. However, there is a lack of uniformity with regard to terminology and forms of integration. Therefore, this article investigates how geography in schools has developed through its efforts of integration and finally derives a conceptual approach for systematising forms of integration in the field of social sciences. In addition, a qualitative analysis is undertaken of all previously published curricula in Germany for combined courses for social science subjects in oder to determine forms through which education in geography is taken into account in curricula.
Keywords: history of Geography; curriculum; Geography Education; subject groups; subject integration